Helpful, Unnecessary, or Harmful: A Systematic Review of the Effects of Prescription Drug Monitoring Program Use on Opioid Prescriptions - Nina Z. Y. Smith; J. Douglas Thornton; Susan H. Fenton; Debora Simmons; Tiffany Champagne-Langabeer (MDPI AG, 2023)
Prescription drug misuse is a global problem, especially in the United States (US). Clinician involvement is necessary in this crisis, and prescription drug monitoring programs (PDMPs) are a recommended tool for the prevention, recognition, and management of prescription opioid misuse. However, because of the plethora of differences between different PDMPs, research on their effects is mixed. Yet, despite varied evidence, policy on PDMP use is trending stricter and more comprehensive. We aimed to identify patterns in the research to inform clinicians and policy. Through a systematic review of four literature databases (CINAHL, Cochrane Database, Embase, and Medline/OVID), we found 56 experimental and quasi-experimental studies published between 2016 and 2023 evaluating PDMP effects on clinician behavior. To address study heterogeneity, we categorized studies by type of intervention and study outcome. The review suggests that more comprehensive PDMP legislation is associated with decreases in the number of opioid prescriptions overall and the number of risky prescriptions prescribed or dispensed. However, this review shows that much is still unknown, encourages improvements to PDMPs and policies, and suggests further research.